Morbidity of community-acquired pneumonia - Baskaran, Vadsala (2021)
Background Community-acquired pneumonia (CAP) accounts for 5-12% of lower respiratory tract infections presenting to primary care in the UK. Of patients who present to their GP with suspected CAP, 22- 42% are referred to hospital for further management in the UK. The majority of patients ( ̴90%) admitted for CAP survive to hospital discharge. However, little is known about the morbidity related to recovery from pneumonia.